SETD7 drives diabetic endothelial dysfunction through FBXO45-mediated GPX4 ubiquitylation - Wen Zhong; Ruoxue Chen; Jialin Zhao; Yuyu Zhang; Jintao He; Huibin Wang; Feng Zhu; Chunxiang Fan; Xinhua Liu (Cardiovascular Diabetology)
Abstract Background Vasculopathy is the most prevalent complication of diabetes. Endothelial damage, a primary contributor to hyperglycemic vascular complications, impacts macro- and micro-vasculatures, causing functional impairment of multiple organs. SETD7 was initially identified as a transcriptional activator based on its ability to methylate histone 3 lysine 4. However, its function in the context of diabetic endothelial dysfunction remains poorly understood. This study aims to elucidate the involvement and underlying mechanisms of SETD7 in diabetic endothelial dysfunction. Methods SETD7 knockout mice were generated to investigate the effects of SETD7 on Streptozotocin (STZ)-induced hyperglycemia and vascular endothelial injury. Endothelial-specific SETD7 interruption adeno-associated virus (AAV) system was utilized to investigate the effects of SETD7 on diabetic vascular endothelial injury in BKS-DB(Lepr) KO/KO (db/db) mice. In vitro manipulation of SETD7 activation or knockdown was conducted to assess its regulation on the lipid peroxidation, oxidative stress, and cell function of primary rat aortic endothelial cells (RAECs) under high glucose conditions. Results Our study revealed that knockout and endothelial deficiency of SETD7 partially restored damaged vascular function and attenuated the inflammatory response caused by high glucose in both STZ-induced and db/db mice. Moreover, SETD7 activation aggravated oxidative stress injury and resulted in profound dysfunction through Glutathione Peroxidase 4 (GPX4)-mediated lipid peroxidation in RAECs. Mechanistically, SETD7 deficiency reduced p53 mono-methylation and blocked FBXO45 transcription, thereby inhibiting the protein degradation of GPX4 and subsequent lipid peroxidation as well as oxidative stress. Conclusions In summary, our study demonstrates that SETD7-p53-FBXO45-GPX4 is involved in high glucose-induced oxidative stress injury and exacerbated endothelial dysfunction, which offering great significance for mitigating hyperglycemia-induced endothelial damage. Graphic abstract